2004
DOI: 10.1309/9w8d-3xcv-lra3-858a
|View full text |Cite
|
Sign up to set email alerts
|

TTF-1, Cytokeratin 7, 34bE12, and CD56/NCAM Immunostaining in the Subclassification of Large Cell Carcinomas of the Lung

Abstract: We selected a 4-stain immunopanel including thyroid transcription factor (7ITF)-], cytokeratin (CK)7, 34betaE12, and CD56/neural cell adhesion molecule(NCAM) to subclassify a series of 45 pulmonary large cell carcinomas (LCCs) on bronchial biopsy. All cases consisted of a large tumor cell proliferation with abundant cytoplasm, vesicular nuclei, and prominent nucleoli. Immunohistochemically, 27 tumors (60%)were subclassified as adenocarcinoma (7TF-1 +/CK7+,24; CK7+ only, 3), 10 (22%) as squamous cell carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 47 publications
1
33
0
1
Order By: Relevance
“…7 Several recent studies showed that immunostains (and previously electron microscopy 42 ) can reveal the line of differentiation as adenocarcinoma vs squamous cell carcinoma in the majority of large cell carcinomas. 26,36,43,44 The proposed TTF-1/p63 algorithm could be used to determine biological identity within the large cell carcinoma, but this needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several recent studies showed that immunostains (and previously electron microscopy 42 ) can reveal the line of differentiation as adenocarcinoma vs squamous cell carcinoma in the majority of large cell carcinomas. 26,36,43,44 The proposed TTF-1/p63 algorithm could be used to determine biological identity within the large cell carcinoma, but this needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Both of these gene families have been used in numerous histopathological studies to characterize various types of cancer, including lung adenocarcinomas. 31,32,33 Noting this, we reasoned that expression data on these families, together with data on TTF-1 expression, would provide fundamental information on the properties of lung adenocarcinoma cells. Toward this end, we extracted expression profile data for the cytokeratin and MUC family genes and examined the relative expression levels of these genes in the cell lines.…”
Section: The Expressions Of Ttf-1 Cytokeratin 7 and Muc1 Genes Corrmentioning
confidence: 99%
“…As a result, LCC contains a heterogeneous mix of entities, which complicates any potential characterization studies or clinical trials. In addition to gene expression-based approaches, [11][12][13][14][15][16][17] multiple studies [18][19][20][21][22][23][24][25][26][27] have shown that LCC can be reclassified as ADC, SQC, or large cell neuroendocrine carcinoma by immunohistochemistry. The widespread use of immunohistochemistry in diagnostic practice may explain the decreasing incidence of LCC.…”
mentioning
confidence: 99%